Decreased Lipid Profile and Oxidative Stress in Healthy Subjects Who Underwent Whole-Body Cryotherapy in Closed Cryochamber with Subsequent Kinesiotherapy. (14th August 2019) - Stanek, Agata; Romuk, Ewa; Wielkoszyński, Tomasz; Bartuś, Stanisław; Cieślar, Grzegorz; Cholewka, Armand
Abstract : Objective . The aim of the study was to estimate the impact of whole-body cryotherapy (WBC) and subsequent kinesiotherapy on oxidative stress and lipid profile when performed in a closed cryochamber on healthy subjects. Material and Methods . The effect of ten WBC procedures lasting 3 minutes a day followed by a 60-minute session kinesiotherapy on oxidative stress and lipid profile in healthy subjects (WBC group, n = 16 ) was investigated. The WBC group was compared to the kinesiotherapy only (KT;n = 16 ) group. The routine parameters of oxidative stress (antioxidant enzymatic and nonenzymatic antioxidant status, lipid peroxidation products, total oxidative status (TOS), and oxidative stress index (OSI)) and lipid profile were estimated one day before the beginning and one day after the completion of the research program. Results . After treatment, in the WBC group, a significant decrease of oxidative stress markers (TOS and OSI) and a significant increase of total antioxidant capacity were observed. The activity of plasma SOD-Mn and erythrocyte total SOD increased significantly in the WBC group. In the KT group, the erythrocyte activity of total SOD, CAT, and GR decreased significantly after the treatment. The levels of T-Chol and LDL-Chol decreased significantly after treatment in both groups, but the observed decrease of these lipid parameters in the WBC group was higher in comparison to the KT group. The level of TG decreased significantly after treatment in the WBC group only. Conclusion . WBC performed in a closed cryochamber followed by kinesiotherapy improves lipid profile and decreases oxidative stress in healthy subjects.